Hanan al-cinema : affections for the moving image - Marks, Laura U., 1963- (Cambridge, Massachusetts ; London, England : The MIT Press, 2015)
An examination of experimental cinema and media art from the Arabic-speaking world that explores filmmakers' creative and philosophical inventiveness in trying times.
Introduction -- Cinematic friendships : intercessors, collectives, perturbations -- The language of terrorism : Elia Suleiman's film practice -- Arab cinema unfolds -- Mohamed Soueid's cinema of immanence -- Communism, dream deferred -- Can cinema slow the flow of blood? -- Asphalt nomadism -- Archival romances -- Hala Elkoussy : framing chaos -- Hassan Khan : the social contract -- Mounir Fatmi : protective aniconism -- Algorithm, decryption, glitch -- Images in motion, from haptic vision to networked space -- Sherif El Azma : a cinema of cruelty -- What can a body do?
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Motion pictures -- Arab countries -- History -- 21st century; Documentary films -- Arab countries -- History -- 21st century; Motion picture industry -- Arab countries -- History -- 21st century; Video art -- Arab countries -- 21st century; Cinéma -- États arabes -- Histoire -- 21e siècle.; Cinéma -- Industrie -- États arabes -- Histoire -- 21e siècle.; Art vidéo -- États arabes -- 21e siècle.; PERFORMING ARTS -- Reference; Documentary films; Motion picture industry; Motion pictures; Video art; Arab countries; Arabländerna.; Dokumentärfilm.; Filmindustrin, Arabländerna.; 2000-2099; ARTS/Photography & Film/History, Theory & Criticism; DIGITAL HUMANITIES & NEW MEDIA/New Media Art; CULTURAL STUDIES/Global Studies; History